Global prevalence of malnutrition in older adults: A comprehensive systematic review and meta-analysis - Nader Salari; Niloofar Darvishi; Yalda Bartina; Fatemeh Keshavarzi; Melika Hosseinian-Far; Masoud Mohammadi (Public Health in Practice)
Objectives: Early detection and management of malnutrition is essential for the general health and well-being of the elderly. Various studies have reported different types of malnutrition prevalence in the elderly. the present study was aimed to determine the prevalence of malnutrition in the world’ elderly through conducting a systematic review study and meta-analysis.Study Design: systematic review and meta-analysis. Methods: In this review study, data was extracted by searching in national and international databases of SID, MagIran, Google scholar, ScienceDirect, Scopus, PubMed and Web of Science (WoS) without time limit until August 25, 2023. For analysis, Begg and Mazumdar test at a significance level of 0.1 and the corresponding Funnel plot were used. Data analysis was performed with Comprehensive Meta-Analysis software (Version 2). Results: In the review of 98 studies with a total sample size of 79976, the prevalence of malnutrition in the world's elderly was obtained as 18.6 % (95 % confidence interval: 16.4-21.1 %), so that the highest prevalence of malnutrition was in the elderly of Africa with 35.7 %, followed by the America with 20.3 %. According to the subgroup analysis regarding the indicators of malnutrition in the elderly, the highest prevalence of malnutrition in the elderly was obtained as 39.9 % according the NRS-2002 index. Conclusion: Therefore, in addition to raising awareness among families about malnutrition in the elderly and its negative effects on the quality of life of the elderly, it is necessary to take the necessary measures to provide more care for the elderly and also to pay serious attention to the importance of nutrition during old age.